2015
DOI: 10.3109/21691401.2015.1029630
|View full text |Cite
|
Sign up to set email alerts
|

Piper betle-mediated synthesis, characterization, antibacterial and rat splenocyte cytotoxic effects of copper oxide nanoparticles

Abstract: The study reports a simple, inexpensive, and eco-friendly synthesis of copper oxide nanoparticles (CuONPs) using Piper betle leaf extract. Formation of CuONPs was confirmed by UV-visible spectroscopy at 280 nm. Transmission electron microscopy (TEM) images showed that the CuONPs were spherical, with an average size of 50-100 nm. The scanning electron microscopy (SEM)-energy dispersive spectroscopy (EDS) peak was observed approximately at 1 and 8 keV. The X-ray diffraction (XRD) studies indicated that the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…At 50-ll concentration, the viability of HEK 293 cells was decreased to 83.5 ± 1.66% compared to the initial level, and longer exposure resulted in increased toxicity to the cells (data not shown). The results are consistent with previous studies reporting cytotoxic potential of metallic nanoparticles (Praburaman et al 2015).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…At 50-ll concentration, the viability of HEK 293 cells was decreased to 83.5 ± 1.66% compared to the initial level, and longer exposure resulted in increased toxicity to the cells (data not shown). The results are consistent with previous studies reporting cytotoxic potential of metallic nanoparticles (Praburaman et al 2015).…”
Section: Resultssupporting
confidence: 93%
“…Numerous studies have reported the antibacterial and antifungal activity of metallic nanoparticles; for example, Cr 2 O 3 nanoparticles inhibit the growth of Escherichia coli (Ramesh et al 2012) and Pseudomonas aeruginosa (Rakesh et al 2013), Ag nanoparticles significantly inhibit growth of Colletotrichum coccodes, Monilinia sp., Pyricularia sp., B. cereus., P. aeruginosa, and Bacillus anthracis (Lee et al 2013;Singh et al 2015), Au nanoparticles inhibit the growth of Staphylococcus aureus, E. coli, and P. aeruginosa (Bindhu andUmadevi 2014, Singh et al 2014), and CuO nanoparticles inhibit the growth of phytopathogens Ralstonia solanacearum and Xanthomonas axonopodis (Praburaman et al 2015). Hence, the objectives of this study were to (i) synthesize Cr(III) nanoparticles using wastewater from electroplating industries under optimized conditions, (ii) characterize the synthesized Cr(III) nanoparticles, and (iii) evaluate the antibacterial and cytotoxicity of the synthesized Cr(III) nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the presence of 100 g/mL of AgNPs significantly inhibits the cells growth by more than 90% ( Figure 6). Several studies have reported that AgNPs may induce reactive oxygen species and cause damage to cellular components leading to cell death [26][27][28][29]. Nevertheless, this is the first report on cytotoxicity effects of green synthesized AgNPs using CSOC extract against rat splenocytes.…”
Section: Cytotoxicity Of Agnpsmentioning
confidence: 95%
“…betle leaf extract efficiently inhibited the growth of phytopathogens such as Xanthomonas axonopodis and Ralstonia solanacearum and also exhibited a cytotoxic effect on rat splenocytes by decreasing cell viability to 94% at 300 μg/ml. 234 Silver nanoparticles coated with polyaniline (AgNP) synthesis from P . betle leaf extracts were evaluated for antimicrobial potency.…”
Section: Nanoformulationsmentioning
confidence: 99%